Effect of Microwave Treatment on Microbial Contamination of Honeys and on Their Physicochemical and Thermal Properties - Paz Moliné María de la; Fernández Natalia Jorgelina; Medici Sandra Karina; Fasce Diana; Gende Liesel Brenda (Polish Journal of Food and Nutrition Sciences)
In recent years, microwave heating has become a common method for pasteurization and sterilization of food. Honey is a sweet substance produced by worker honeybees from nectar of flowers. The major microbial contaminants include moulds and yeasts, as well as the spore-forming bacteria, being their counts indicative of honeys’ commercial quality and safety. Paenibacillus larvae is also of interest since it causes American foulbrood (AFB) in honeybee larvae. The main quality factors that are used in the honey international trade are moisture, hydroxymethylfurfural content (HMF), and enzymatic indices. Moreover, honey exhibits several thermal events, the most important being the glass transition temperature (Tg). The aim of this work was to evaluate microwave effect (800 watts during 45 and 90 seconds) on microbial content in particular over P. larvae spores retained in honey, and on physicochemical and thermal properties. Microwave promoted a decrease of microbial count with time of exposure, including P. larvae. Moisture content diminished after treatment, while Tg increased linearly, and acidity decremented in the majority of cases. Honeys darkened and HMF exceeded the permissible value. Diastase and glucose-oxidase enzymes were totally inactivated by microwave treatment.